Evaluation of naturally occurring IgG anti-Vi antibody titers as predictors and correlates of typhoid fever in Dhaka, Bangladesh - Farhana Khanam; Natasha Y. Rickett; Faisal Ahmmed; Md Taufiqul Islam; Cecilia Kathure Mbae; Justin Im; Asma Binte Aziz; Beatrice Ongadi; Fahima Chowdhury; Ashraful Islam Khan; Afroza Akter; Md Golam Firoj; et al. (BMC Infectious Diseases)
Abstract Background When delivered through vaccination Vi-polysaccharide antigen of Salmonella enterica serotype Typhi protects against typhoid by inducing IgG anti-Vi antibodies. We aimed to determine whether the presence of antibodies following natural infection is associated with a lower incidence of typhoid fever in endemic regions. Methods We analyzed data from a cohort study of typhoid fever conducted in Dhaka, Bangladesh. Plasma IgG anti-Vi antibodies were measured using a standard enzyme-linked immunosorbent assay in random serosurveys of a population that had not previously received typhoid vaccination. Participants were followed for up to 20 months for culture-confirmed typhoid fever. The receiver operating characteristic (ROC) curve and Cox proportional hazard models were used to evaluate the associations between antibody levels and typhoid risk. Results The ROC analysis revealed that IgG anti-Vi antibody titers were predictive of typhoid risk among the 8,261 serosurvey participants (area under the curve: 0·63; 95% confidence interval (CI): 0·58─0·67). Detection of any antibodies was associated with a lower risk of typhoid in crude analyses (hazard ratio (HR): 0·13; 95% CI: 0·03─0·52), though this association declined after adjustment (HR: 0·32; 95% CI: 0·07─1·40). A positive correlation was observed between IgG anti-Vi titers and age (correlation coefficient 0·35; p < 0·001), with a stepwise increase in detectable antibodies by age, ranging from 12·0% (280/2,333) in children under 5 years to 54·2% (463/854) in individuals 50 years and older (p < 0·001). Conclusions In typhoid-endemic populations, IgG anti-Vi antibodies may indicate natural immunity to typhoid. The increasing seroprevalence with age suggests that these antibodies could serve as markers of cumulative past typhoid infections. Future research should explore these possibilities. Clinical trial number Not applicable.